Pectoralis major tendon rupture in a weight lifter: a rare case. - Pedrazzini, Alessio; Banchi, Massimo; Bertoni, Nicola; Pedrabissi, Bianca; Simo, Henry Claudel Yewo; Medina, Vanni; Bonassi, Pietro; Tocco, Silvio; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2017)
Pectoralis major tendon (PMT) rupture is a rare event, and it was originally described by Patisser in 1822. The PMT is a thick lamina, which has two origins, one from the clavicle and the other from the ribcage sternum. PMT lesions are classified according to 3 levels of severity: Type 1 is contusions and strains, Type 2 is a partial tear and Type 3 is a complete tear. Diagnosis is made through a clinical examination which comprises a positive response to pain upon pressure over the axilla recess, the presence of bruising and limited motion, and is completed with an MRI. Type 3 injuries are treated exclusively through surgery, while Type 1 and 2 lesions are treated conservatively. In this article, we describe a rare case of PMT rupture in a 39-year-old weight lifter, the surgical treatment that was carried out through an open access at the Pectoralis and Deltoid junction and anchor suture, the post-surgical rehabilitation program and a 1-year follow-up assessment at which point return to sport was achieved.